Food web changes associated with drought and invasive species in a tropical semiarid reservoir - Bezerra, Luis Artur Valões; Angelini, Ronaldo; Vitule, Jean Ricardo Simões; Coll, Marta; Sánchez-Botero, Jorge Iván (Hydrobiologia, 2018)
Fish and invertebrates are introduced in freshwaters around the world for commercial purposes, despite widely known impacts on food webs and biological invasions. As a proxy for artificial environments, we modeled a typical reservoir in a Brazilian semiarid region using an ecosystem approach. We compared the role of native and non-native invasive species (NIS) in the food web, between dry and wet periods, and under the influence of an extreme drought period (from 2011 to 2015), simulating the variation in fish biomasses due to decreasing consumption. Key ecosystem groups were fishes (mainly NIS), birds, and insects. Nutrient cycling was dependent on invaders, while the trophic structure was detritus based during the drought. Biomass of detritivores was almost two times higher than herbivores, and native fish species decreased abruptly in response to invaders and volume variation. The dominance of low-trophic levels (TLII) and tilapia— Oreochromis niloticus (Linnaeus, 1758) and other tilapiines—resulted from interactions among invaders, feeding behavior on benthos, and environmental seasonality, tending toward biotic homogenization (“benthification”) at the ecosystem level. An increasing relevance of detritivores with cascading effects in ecosystems subject to drought, multiple introductions, and ubiquitous food sources has clear implications for the fisheries and the water quality.